ANALISIS KRITIS NORMAN FAIRCLOUH PADA BERITA PERNIKAHAN SIRI ARTIS LESTI KEJORA DENGAN RIZKY BILLAR - Alo Karyati Supardi; Yumna Rasyid; Miftahalulkhairah Anwar (JURNAL KOMUNIKATIO, 2022)
This study discussed the news in several online media news regarding the unregistered marriage between the artist couple Lesti Kejora and Rizky Billar. The purpose of this study was to determine the critical analysis of Norman Fairclouh on the Marriage News of Artist Siri Lesti Kejora with Rizky Billar. The study used Norman Fairclough's Critical Discourse Analysis to analyze articles in five online news stories. The object of this research was the news headlines about the marriage of Rizky Billar and Lesti Kejora on five online news websites, namely Sosok.id.com, tribunnew.com, detik.com, Kompas.com, and tabloidbintang.com. The research method used in this research was descriptive qualitative. The data collection technique started from looking for similar stories in several online news stories. The data analysis technique in this research was to analyze similar news, and then the news is analyzed for the pros or cons of reporting one by one. The analysis of the five news articles found that the ideological, cultural, and legal aspects were present through the views of the internet community (netizens) on the procedures and continuity of unregistered marriage activities. The conclusion is the analysis of the five news reports found that news coverage was not always objective but always had the news writer's point of view. Aspects of culture, ideology and law are aspects that become the theme of the news.